Direito à privacidade e à proteção de dados na cultura do algorítmo: desafios de adequação face à Lei Geral de Proteção de Dados Pessoais (LGPD) - Forcelini, Letícia Spagnollo (2022)
This Dissertation is part of the Jurisdiction Research Line Constitutional and Democracy. The scientific objective of this study was to analyze the main challenges of adaptation, especially of cooperative systems, given the legislative innovations imposed through the validity of the General Law for the Protection of Personal Data (LGPD). The first chapter portrays the current sociological bias, presenting aspects relating to virtual society. The main transformations occurring in the media of communication and information, as well as the way in which these changes also reflected major impacts on consumer relations. The emergence of the internet is mainly responsible for massification of network contracts. Contextualized about the role fundamental promoted by algorithms in the processing of personal data in the digital scope and, alongside this, the (hyper) vulnerability of the consumer was presented in this medium. Chapter 2 identified how personal data is protected in current Brazilian legal system, based on the study and understanding of the Law General Protection of Personal Data (LGPD). Furthermore, a comparative parallel between the Brazilian legal provision and the European regulation, which is consolidated through the General Data Protection Regulation (GDPR). Node chapter 3 addressed the main consequences caused by the transformations technological technologies in the social environment, through the democratization of credit and the consequent problem of over-indebtedness of the population. It was also discussed about the cooperativism, with an emphasis on the credit sector, understanding it as a effective tool for financial and social inclusion. The objective was to analyze the main impacts and implementation and adaptation challenges generated by these cooperative systems, caused by the validity of the LGPD, seeking to guarantee of effective consumer protection. It was concluded that the LGPD aims, in real way, protect the Brazilian population by regulating how data of holders will be processed by organizations, including providing for penalties for non-compliance with established standards. It was evident, however, that the aforementioned legal diploma aims to provide greater security and reliability to users, members, customers, employees and all people who offer their data to an organization. It is a mechanism capable of reinforcing the national consumer protection system, through its specificity in protection and privacy of personal data, revealing itself as a possibility of promoting effective protection, which implements the rights fundamental principles established by the Federal Constitution of the Republic.